Fish and Bivalve Therapeutants in Freshwater Mussel Captive Breeding—A First Summary of Practical Experiences in European Facilities - Marco Denic; Keiko Nakamura; Catarina Varela-Dopico; Ben Strachan; Daniel Daill; Jakob Gaehrken; John Taylor; Felix Grunicke (Diversity, 2024)
A significant part of freshwater mussel populations has strongly declined and many species are severely threatened nowadays. Captive breeding programs often form a central part of conservation strategies. As the life cycles of many mussel species include an obligate parasitic phase, host fish health is a crucial component of successful mussel breeding efforts. However, information about the safe application of fish therapeutants in mussel captive breeding is scarce. This article summarizes information about practical experiences in Europe. In total, eight different therapeutants were used to treat infestations of eight pathogens. Treatment success varied depending on pathogen and prevalence when treatments were initiated. Mussels did not seem to be affected by treatments, especially as long as they remained encysted. In a second step, Virkon S was applied to treat a fungal infection in tanks with brown trout (Salmo trutta) carrying encysted freshwater pearl mussel (Margaritifera margaritifera) glochidia and to disinfect juvenile mussel rearing containers. In both cases, mussels were not harmed and treated fish fully recovered. Results indicate that certain therapeutants can be used safely and successfully at different stages of breeding cycles. Nevertheless, there is still a lack of standard protocols, which would improve efficiency and the safety of treatments.